Supply Chain Model of Fish Caught Landed at The Pelabuhan Perikanan Samudera (PPS) Cilacap, Central Java - Mukhlisa A Ghaffar; Widiya Wanti; Erna (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The purpose of this study is to analyze the supply chain model of fish caught landed at PPS Cilacap. The method used in this study is a survey method with purposive sampling data collection techniques. The results showed that the management of the supply chain of catches landed at Ocean Fishing Port PPS Cilacap has been formed downstream of fishermen's catches to the hands of domestic and foreign consumers. Parties who have a strategic role in ensuring the fulfillment of fish are fishermen as the main supplier and ship owners as collectors and distributors. PPS Cilacap has also carried out its role in collecting fishery products and delivering information to all parties in need through Pusat Informasi Pelabuhan Perikanan (PIPP). The distribution of fish abroad opens up opportunities to increase state income from the export of fishery products and this also shows the fulfillment of the operational criteria of PPS Cilacap as a type A (ocean) fishing port based on government regulations on fishing ports